An EKF observer to estimate semi-autogenous grinding mill hold-ups. (March 2017) - le Roux, J.D.; Steinboeck, A.; Kugi, A.; Craig, I.K.
Abstract : Highlights: A non-linear observer model of a semi-autogenous grinding mill is developed. The model measurements are the mill filling, discharge flow-rate and density. The model states and parameters are linearly observable from these measurements. An EKF is applied in simulation to estimate model states and parameters. The grinding media, solids and water hold-up in the mill can be reliably estimated. Abstract: A non-linear observer model of a semi-autogenous grinding mill is developed. The observer model distinguishes between the volumetric hold-up of water, solids, and the grinding media in the mill. Solids refer to all ore small enough to discharge through the end-discharge grate, and grinding media refers to the rocks and steel balls. The rocks are all ore too large to discharge from the mill. The observer model uses the accumulation rate of solids and the mill's discharge rate as parameters. It is shown that with mill discharge flow-rate, discharge density, and volumetric hold-up measurements, the model states and parameters are linearly observable. Although instrumentation at the mill discharge is not yet included in industrial circuits because of space restrictions, this study motivates the benefits to be gained from including such instrumentation. An extended Kalman filter is applied in simulation to estimate the model states and parameters from data generated by a semi-autogenous mill simulation model from literature. Results indicate that if sufficiently accurate measurements are available, especially at the discharge of the mill, it is possible to reliably estimate grinding media, solids and water hold-ups within the mill. Such an observer can be used as part of an advanced process control strategy.